The work placement effect towards the work environment of Grand Indonesia Industry Company - Damayanti, Fitria; R, Nurjanah (Management and Entrepreneurship: Trends of Development, 2019)
This study has purpose to find out the effect of work placement towards the work environment. Due to the hypothesis of the research, the right placement and position are able to help the company to achieve the goals. Afterward, the methods used are associative method and descriptive method. The indicator of work placement that is used in this study is synthesis of determining work location, determining work position, and assigning. The number of populations involving in this study is 268 and sample is 160 respondents. Then, the result of the study shows that the work placement based on Grand Indonesia Industry Company employees’ responds in determining work location, work position and assignment indicators are 3896 which is categorized as good enough. Furthermore, the work environment in Grand Indonesia Industry Company based on Grand Indonesia Industry Company employees’ responds on facilities and work implementation are 4034 which is categorized as very good. However, the analysis result of work placement correlation towards the work environment is rX1. Y-0,22 included as low category. Originality and value of the research defined by the obtained results and discussion, according to which, it is supposed to increase the work placement for employees especially in assignments, determining the work position of employees so that employees are always passionate to work. It is also recommended to improve the work environment, especially in the implementation of work, work infrastructure so that employee performance can increase. Practical and social implications of the research are added by the suggestion to improve the work environment, especially in the implementation of work, work infrastructure so that employee performance can increase.JEL Classification: M52, M53, M54